Answer:
Hence Proved △ SPT ≅ △ UTQ
Step-by-step explanation:
Given: S, T, and U are the midpoints of Segment RP , segment PQ , and segment QR respectively of Δ PQR.
To prove: △ SPT ≅ △ UTQ
Proof:
∵ T is is the midpoint of PQ.
Hence PT = PQ ⇒equation 1
Now,Midpoint theorem is given below;
The Midpoint Theorem states that the segment joining two sides of a triangle at the midpoints of those sides is parallel to the third side and is half the length of the third side.
By, Midpoint theorem;
TS║QR
Also, ![TS = \frac{1}{2} QR](https://tex.z-dn.net/?f=TS%20%3D%20%5Cfrac%7B1%7D%7B2%7D%20QR)
Hence, TS = QU (U is the midpoint QR) ⇒ equation 2
Also by Midpoint theorem;
TU║PR
Also, ![TU = \frac{1}{2} PR](https://tex.z-dn.net/?f=TU%20%3D%20%5Cfrac%7B1%7D%7B2%7D%20PR)
Hence, TU = PS (S is the midpoint QR) ⇒ equation 3
Now in △SPT and △UTQ.
PT = PQ (from equation 1)
TS = QU (from equation 2)
PS = TU (from equation 3)
By S.S.S Congruence Property,
△ SPT ≅ △ UTQ ...... Hence Proved